MEDICINAL CHEWING GUM AS A PROMISING DRUG DELIVERY SYSTEM (REVIEW) - N. L. Solovieva; M. S. Sokurenko (Разработка и регистрация лекарственных средств, 2019)
Medicated chewing gum (MCG) are an alternative to solid dosage forms for oral use. In the Pharmacopoeia of the United States submitted an article on chewing gum of nicotine. A monograph of this drug form is available in Belarusian and European Pharmacopoeias. The article presents the analysis of the literature on the use MCG as delivery system of drugs, excipients for the manufacture of MCG, as well as the schemes for the production of medicinal chewing gum and tests of their quality.